An extended Linear Quadratic Regulator with zone control and input targets. (May 2015) - Capron, Bruno Didier Olivier; Odloak, Darci
Highlights: A controller that combines LQR and MPC in a single strategy is proposed. The controller allows input saturation and zone control of the outputs. Stability is assured for both open-loop stable and unstable systems. Input targets can also be included. Abstract: This paper focuses on the application of the Linear Quadratic Regulator (LQR) in industrial process systems where one has zone control of the outputs and input economic targets as well as constraints on the inputs and input moves. In the approach proposed here, the LQR is combined with the Model Predictive Control (MPC) in a framework where the system outputs are controlled through the LQR state feedback control law and the output set points are manipulated by the MPC to enforce the input constraints and input targets. The performance of the proposed controller is tested through the simulation of the control of an industrial deisobutanizer column.